Female sex hormones and periodontal health-awareness among gynecologists – A questionnaire survey - Sonali N. Patil; Nagaraj B. Kalburgi; Arati C. Koregol; Shivaraj B. Warad; Sandeep Patil; Mahesh S. Ugale (Saudi Dental Journal)
Sex hormones play an important role in periodontal health and disease. For example, puberty, menses, pregnancy, menopause, and oral contraceptive use influence a woman’s periodontal health. Periodontal infection has also been associated with adverse pregnancy outcomes. Subsequently, it is important that gynecologists are educated about hormonal effects on women’s oral health. The current study assessed gynecologist’s awareness regarding the effect of female sex hormones on periodontal health, preterm delivery, and maternal periodontal disease. Methods: Gynecologists from the Bagalkot district of the Karnataka state, India, completed a questionnaire regarding female hormonal and periodontal health. Respondents were divided into two groups: Group A (doctors that practiced at a medical college or hospital) and Group B (doctors that practiced at private hospitals). Out of 73 gynecologists, 62 (85%) completed the survey, with 19 (30.6%) participants in Group A and 43 (69.4%) participants in Group B. Survey responses were collected in the presence of the investigator, and data between the groups were statistically compared. Results: Our findings showed that most gynecologists were aware and concerned about female patient’s oral health during various hormonal phases. However, gynecologists practicing at medical colleges and hospitals (Group A) had significantly greater health awareness than doctors practicing at private hospitals (Group B). Conclusion: Women have special periodontal health care considerations, and there is a need for better oral health education among caregivers. Our results suggest that increasing dental health awareness among gynecologists would significantly improve women’s health and pregnancy outcomes. Keywords: Periodontal health, Pregnancy, Periodontal disease, Preterm low birth weight, Gynecologist, Questionnaire